Pengembangan Instrumen Tes Literasi Sains Berbasis Kearifan Lokal Di Probolinggo - Maya Ningsetyo; Titin Sunarti (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The purpose of this study was to describe the theoretical and empirical validity of the developed science literacy test instrument related to local wisdom in Probolinggo. This type of research is Research and Development with development steps modified by Sugiyono (2019). The test subjects of this study were students of class XII SMAN 1 Dringu. The development results that have been validated by 3 validators obtained 15 questions in the form of descriptions. The results of theoretical validity obtained mode scores in the domains of material, construction, and language 4, 4, and 3 respectively with very good and good categories. Theoretically valid test instruments were tested on 30 students. The results of the empirical instrument analysis are, (a) The level of difficulty of the items obtained is 0.31 to 0.68 with a moderate category, (b) The distinguishing power of the items obtained is an index of distinguishing power of -0.06 to 0.50 with low, medium, good enough, and very good categories, (c) The reliability of the instrument obtained of 0.86 with the instrument declared reliable, (d) The validity of the items obtained a correlation number of 0.01 to 0.84 with very low, low, sufficient, high, and very high categories.